58A CRYPTOGRAPHIC TECHNIQUE BASED ON AVL TREE - Abdulla, Sura; Al Barrak, Alyaa (Iraqi Journal of Science, 2024)
Cryptography provides confidentiality and privacy by scrambling information. This paper presents a new cryptographic method using English letters frequencies and AVL tree to provide an increased level of confidence for exchanging information over networks especially internet which is insecure network.Experiment results of the proposed method provide better security than the classical methods depending on number of parts used to build the key in this method.